2019
DOI: 10.1177/0361198119837235
|View full text |Cite
|
Sign up to set email alerts
|

A Pedestrian Exposure Model for the California State Highway System

Abstract: For this study, we developed one of the first statewide pedestrian exposure models, using log-linear regression to estimate annual pedestrian crossing volumes at intersections on the California State Highway System. We compiled a database of more than 1,200 count locations, one of the largest ever used to create a pedestrian volume mode. We initially evaluated 75 explanatory variables for the model. The final model is based on the three land-use variables (employment density, population density, number of scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Pedestrian demand models are most common at the local level (7, 13-18), but they could also be applied across metropolitan regions and states (10). To our knowledge, California currently has the only statewide pedestrian volume model (19).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedestrian demand models are most common at the local level (7, 13-18), but they could also be applied across metropolitan regions and states (10). To our knowledge, California currently has the only statewide pedestrian volume model (19).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Common explanatory variables include measures of population or housing density, employment density, commercial retail density, and transit stop proximity and service frequency (4, 7). Explanatory variables are often collected at several different distances from the count location (i.e., different buffer widths) to identify the most influential scale of a particular characteristic on pedestrian activity (3,4,15,(17)(18)(19)(20). Many models include these common variables, but the magnitude and direction of influence of these variables in specific models can be different depending on the study area (4).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, safety analysis requires measures of pedestrian exposure at the level of intersections and street segments. If the relationships inherent to direct-demand built-environment models of pedestrian volumes ( 59 , 60 ) are changing, then static estimates of activity may not reflect true pedestrian risk. This is particularly important because preliminary 2020 U.S. traffic safety data show a troubling continued increase in pedestrian deaths despite significant decreases in vehicle distances traveled ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…The total of the overlaps produced the estimates of socioeconomic/demographic variables at each intersection. The specific variables considered included those that had known relationships with pedestrian exposure in the research literature, as identified in Frank et al ( 13 ), Griswold et al ( 14 ), Hampshire et al ( 15 ), and Hankey et al ( 16 ).…”
Section: Data Summarymentioning
confidence: 99%
“…However, direct measures are often expensive and difficult to implement over a large study area (e.g., a city or region). Previous research efforts have successfully developed pedestrian exposure models to address research needs in safety and public health ( 13 16 ). Furthermore, emerging data sources, such as vehicular probe data, have demonstrated applicability as transportation performance monitoring tools ( 17 , 18 ).…”
mentioning
confidence: 99%